(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
Taking into account the fundamental reforms being carried out in the education system and the high expected results, a number of innovations are taking place in our legislation. This article highlights the importance of foreign experience for educational and educational processes and the main aspects of their effective use.